INVENTARISASI POHON UNTUK PENGELOLAAN POHON ASUH DI HUTAN ADAT JORONG GANTIANG NAGARI SIRUKAM KECAMATAN PAYUNG SEKAKI KABUPATEN SOLOK - Adek Leo Siswara; Paus Iskarni (JURUSAN GEOGRAFI FIS UNP, 2019)
This research aims to. 1) to inventory trees as prospective foster trees in Jorong Gantiang Indigenous Forest, Nagari Sirukam. 2) to find out the distribution of foster trees and prospective foster trees in Nagari Sirukam Customary Forest. 3) to find out the management of foster trees and the Jorong Gantiang Nagari Sirukam Customary Forest. This type of research is descriptive with quantitative and qualitative approaches (Mix Method). This research uses primary and secondary data types. Retrieval of tree point data in the field using GPS (Global Positioning System) then for data management of foster trees and Jorong Gantiang Indigenous Forest Nagari Sirukam using interview techniques. The results of this study are: 1) Trees that meet the requirements as foster tree candidates in the Jorong Gantiang Customary Forest are 414 trees and 54 trees are being nurtured. 2) Distribution of prospective foster trees and foster tree trees is displayed in the form of maps after the data is processed with Arc Map software. 3) Management of Customary Forests Nagari Sirukam still uses a customary system in which all regulations governing forests lead to customary regulations.